Efek Kenaikan Harga Terhadap Perilaku Konsumen Dalam Pembelian Bahan Bakar Minyak Kendaraan Pribadi - Pramelani, Pramelani (Jurnal Disrupsi Bisnis, 2023)
The phenomenon of the increase in subsidized fuel by the government during the pandemic has not ended in the spotlight for the people of Indonesia. This is surprising for customers who often use subsidized fuel products such as Petalite. The government raises prices because of rising world prices. Problems in this study also arise which aims to determine the effect of price increases on consumer behavior in purchasing fuel for private vehicles. This study uses a qualitative descriptive method by giving questions via google form to informants who are domiciled in urban Jakarta. The results of the discussion show that consumers object to the fuel price set by the government due to unstable economic conditions and income that has not increased the UMR (Regional Minimum Wage). Consumers seek information and price comparisons from social media. Seeing that the main consideration factor for consumers is price, while the quality factor is below the price factor, consumers still decide to choose the type of subsidized fuel product, namely Petalite.